Digital Marketing: Determinant of E-Wallet Intention for Retail Buyers - Surahman, Surahman; Diah, Ahyar M.; Batoteng, Hendrik; Sarlivia, Sarlivia; Kartina, Desi; Vidhiyanty, Putri M. (Interdisciplinary Social Studies, 2023)
Background: Practically, cell phones not only function as a means of communication and entertainment media but also as a means of payment through various mobile banking and e-wallet applications installed on cell phones. Not only that, but cashless payments can also save time and decrease the time for waiting for change when making transactions. Aim: This study aims to determine the suitability and security received by users of the application of funds and how these two aspects affect the attitudes and behavior of users in the future. Method: The research method used in this study was a survey conducted by distributing questionnaires through online and offline media. The demographics examined in this study are the first users of the E-Wallet Fund application who are domiciled in Samarinda. Both users are classified as having used or are currently using the app. The data the researchers received were 200 respondents, which obtained a total sample data of 160 respondents after sorting. Findings: This study found that attitudes can be influenced by the level of suitability of application users with the lifestyle and habits of users, and behavioral intentions are influenced by how high the level of suitability and also the level of security received and the attitude that arises from the whole process of using it. However, it turns out that this research found that the level of security received did not influence attitudes.